The Contribution of Majelis Munadhoroh wal Maktabah (M3) to Improving the Learning Motivation of Islamic Boarding School Students - S Salman; Wiwik Dyah Andayani (CV. Media Digital Publikasi Indonesia, 2025)
This study examines the contribution of Majelis Munadhoroh wal Maktabah (M3) to improving the learning motivation of students in Islamic boarding schools, focusing on its implementation at Pondok Pesantren Syaichona Moh. Cholil Bangkalan. Using a qualitative case study approach, the research involved M3 program coordinators, teachers, and actively participating students. Data were collected through participatory observation, in-depth interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that M3 enhances both intrinsic and extrinsic motivation through active participation, structured classical text (kitab kuning) literacy development, and the cultivation of Islamic values such as humility (tawadhu’) and brotherhood (ukhuwah). Supporting factors include comprehensive library facilities, the STAISyaichona e-Resource digital platform, conducive learning spaces, and strong institutional support. However, sustaining M3’s impact requires consistent facilitation quality, digital literacy training, and continued stakeholder collaboration. The study concludes that M3 represents a hybrid educational model that preserves traditional pesantren scholarship while integrating modern learning innovations, making it a replicable framework for enhancing student motivation in Islamic education.